APLIKASI KAIDAH "AL-'ADAH MUHAKKAMAH" DALAM KASUS PENETAPAN JUMLAH MAHAR - Kholid Saifulloh (Al-Majaalis : Jurnal Dirasat Islamiyah, 2020)
Al-'adah muhakkamah, literally ‘customary usage is the determining factor’,is one of the five universal maxims of Islamic jurisprudencewhich have a wide branch coverage agreed upon by the scholars.This maxim is built on the basis of custom and local wisdom that exists in every community, where this custom is continuously carried out by the community without any denial from them; it is precisely individuals who violate these customs will be considered "freaks". Therefore, Islam makes the customs of a community a legal basis as long as they fulfill the requirements stipulated by Sharia.The formulation of the problem in this study is about: (1) the definition of the al-'adah muhakkamah maxim, (2) the conditions for applying it, and (3) its application in determining the amount and type of dowry. This paper tries to study a jurisprudence principle and apply it to a jurisprudence problem so as to form a complete understanding of the rules as well as how to apply them in the branch of jurisprudence. The conclusions of this study are: (1) that 'adah is something that happens repeatedly which is accepted by common sense and human nature, (2) an 'adah can become a legal basis if it does not contradict the arguments of the Sharia, it is more often done than abandoned, there is no words of the' adah doer who excludes, and the 'adah must exist at the time the covenant occurs,(3) the rule of al-'adah muhakkamah can be applied to determine the number and types ofmis^ldowries, as well as musamma dowries which are absolutely stated.